Load carrying capacity of partially encased columns for different fire ratings - Abdelkadir, Fellouh (2018)
Partially encased columns have significant fire resistant. However, it is not possible to assess the fire resistance of such members simply by considering the temperature of the steel. The presença of concrete increases the mass and thermal inertia of the member and the variation of temperatures within the cross section, in both the steel and concrete components. The annex G of EN 1994-1-2 [1] allows to calculate the load carrying capacity of partially encased columns, for a specific fire rating time, considering the balanced summation method. New formulas will be used to calculate the plastic resistance to axial compression and the effective flexural stiffness. These two parameters are used to calculate the buckling resistance, assuming the most appropriate buckling curve of EN1993-1-1 [2]. The fínite element method is used to determine which curve best fits the buckling resistance for different fire ratings of 30, 60, 90 and 120 minutes.